Retrospective analysis of clinical characteristics and risk factors of differentiated thyroid cancer in children - Chen, Chun; Hang, Lei; Wu, Yan; Zhang, Qing; Zhang, Yifei; Yang, Jun; Xie, Jin; Lu, Jingrong (Frontiers in Pediatrics, 2022)
Background The incidence rate of children thyroid cancer has an increasing trend. This study aimed to investigate the clinical characteristics and therapeutic approaches of differentiated thyroid cancer (DTC) in Chinese children. Methods. From January 1998 to March 2022, 52 cases undergoing surgical resection in Xinhua Hospital affiliated to Shanghai Jiao Tong University were divided by age (≤7 years old, n=14 and 8-13 years old, n=38). Treatment methods and clinical features were analyzed to evaluate prognostic factors for oncological outcomes. Results. Among the 52 cases, the proportion of local invasion in pre-school group was found to be higher than that in school-age group (p = 0.01). T stage was significantly different between two groups (p＜0.05); the proportion of T1-2 was higher in school-age group (32 cases, 84.2%), while the proportion of T4 was higher in pre-school group (6 cases, 42.8%) relatively. The postoperative complication rate was dramatically higher in pre-school children (p＜0.05). Additionally, total thyroidectomy rate in non-recurrent group was slightly higher than that in recurrent group (p＜0.05). Over half of the recurrent cases had low T stage and low ATA (American Thyroid Association) risk levels at initial diagnosis (78.3% and 51.4%). Conclusion. The local invasion, tumor stage, and recurrent laryngeal nerve (RLN) injury rates of pre-school group were higher than that of school-age group, where young age served as a potential hazard in DTC children. Hence, surgeons should emphasize high-risk features and optimize individualized surgical procedures for DTC children.